Recent advances in understanding proton coupled peptide transport via the POT family. (August 2017) - Newstead, Simon
Highlights: Recent crystal structures reveal insights into ligand promiscuity within the POT family. Selectivity pockets play important roles in peptide recognition and selection. Structural insights into post-translational regulation and mammalian PepT1 and PepT2. Abstract : The POT family of membrane transporters use the inwardly directed proton electrochemical gradient to drive the uptake of essential nutrients into the cell. Originally discovered in bacteria, members of the family have been found in all kingdoms of life except the archaea. A remarkable feature of the family is their diverse substrate promiscuity. Whereas in mammals and bacteria they are predominantly di- and tri-peptide transporters, in plants the family has diverged to recognize nitrate, plant defence compounds and hormones. This promiscuity has led to the development of peptide-based pro-drugs that use PepT1 and PepT2, the mammalian homologues, to improve oral drug delivery. Recent crystal structures from bacterial and plant members of the family have revealed conserved features of the ligand-binding site and provided insights into post-translational regulation. Here I review the current understanding of transport, ligand promiscuity and regulation within the POT family.